2009
DOI: 10.1007/s00421-009-1113-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between surface EMG variables and motor unit firing rates

Abstract: Although surface electromyography (sEMG) is a widely used electrophysiological technique, its physiological interpretation remains somewhat controversial. This study examined the relationship between motor unit firing rates (MUFR) and the root mean square (RMS) amplitude and mean power frequency (MPF) of the sEMG signal in the biceps brachii. Eleven subjects performed maximal isometric elbow flexion while indwelling and sEMG recordings were obtained from the biceps. The RMS amplitude and MPF of the surface sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 41 publications
(55 reference statements)
2
32
1
Order By: Relevance
“…Slight plantar flexion was chosen as previous research has shown that a certain degree of plantar flexion produces a maximal torque and 110° may place the TA closer to optimal length for both maximal evoked and voluntary dorsiflexion torque production, which considers the lever arm length (Marsh et al 1981). A load cell (JR3, Woodland, CA, USA) was secured under the foot plate of which the foot was restrained by a minimally padded steel bar located proximal to the metatarsals for all torque recordings (Christie et al 2009). There were 3 days of testing to assess the reliability of the measures as participants can exhibit a learning effect during maximal strength assessment (Green et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Slight plantar flexion was chosen as previous research has shown that a certain degree of plantar flexion produces a maximal torque and 110° may place the TA closer to optimal length for both maximal evoked and voluntary dorsiflexion torque production, which considers the lever arm length (Marsh et al 1981). A load cell (JR3, Woodland, CA, USA) was secured under the foot plate of which the foot was restrained by a minimally padded steel bar located proximal to the metatarsals for all torque recordings (Christie et al 2009). There were 3 days of testing to assess the reliability of the measures as participants can exhibit a learning effect during maximal strength assessment (Green et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Referring to (7), both the firing rate and intensity are proportional to the square root of E . Interestingly, the exact expression of RMS is actually contained in (7), explaining why RMS can be applied to force estimation, while it also tells the reason why RMS cannot be used to extract firing rate [14]. In effect, (7) builds the relationship between the energy of the control signal (EMG) and that of the output (force or power of muscle).…”
Section: A Oscillator Model Of Emgmentioning
confidence: 99%
“…For this purpose, the semiphenomenological biomechanical/cybernetic model of skeletal muscle established in our previous work [13] would be applied in this paper. As for motion decoding using EMG, many methods, such as RMS, MPF [14], wavelet, fractal, and FIR [15]- [17], etc., have been proposed, while for dynamic control, the real-time performance, robustness, and the accuracy of existent methods are still at issue. To extract reliably the activation level from EMG, a promising way is to find the physical correspondence between the energy of the signal and the power of muscle based on the biomechanical relationship between the firing behavior of motoneuron and muscular contraction [18].…”
Section: Introductionmentioning
confidence: 99%
“…Muscular weakness in T2DM could be due to insulin resistance, intracellular lipid accumulation, mitochondria dysfunction, sarcopenia and neuromuscular impairments (8-15). The electromyographic (EMG) assessment of muscle as a sarcolemma output provides more information about the properties of motor units to control neuromuscular function (16). EMG frequency, an indicator of muscle fiber conduction velocity, and EMG amplitude, a sign of neural excitation (17).…”
Section: Introductionmentioning
confidence: 99%
“…The most electrophysiological assessments in T2DM were limited to measure nerve conduction velocity (20) and compound muscle action potentials that showed reduction in nerve conduction velocity and density of fibers and motor unit in the diabetic polyneuropathy (6, 15, 16). Watanabe et al compared the root mean squared (RMS) activity of vastus lateralis in 10% MVC for 120 seconds between healthy and T2DM by 64 multi-channel EMG.…”
Section: Introductionmentioning
confidence: 99%